What has changed with work during the pandemic? Experiences with telework in a higher education institution (Research, Society and Development, 2022)
In March 2020, the World Health Organization (WHO) declared a global pandemic due to the spread of the coronavirus SARS-CoV-2. To reduce the multiplication of the disease, the government decreed measures of restriction and social isolation in Brazil. As a result, many companies and public institutions had to adopt telework. This research aimed at analyzing, through the perspective of public servants involved with administrative support work in a public institution of higher education, how they experienced telework. The research methodology was qualitative and the data were collected through semi-structured interviews with the institution's employees. The results indicated that remote work has changed the configuration of work relationships between people. The interviewees reported that working at home office brought more flexibility in the performance of their work, besides providing more comfort, since they could work from home. However, they also pointed out: higher levels of stress, anxiety, self-demand and fatigue; accumulation of functions; interference of the family in the work performance, besides the lack of equipment and appropriate place to work. Despite the positive history related to the implementation of telework in some government agencies, public institutions may still find some difficulties in implementing the model of teleworking, mainly due to the structure of the institution and the availability of effective technologies that enable the communication of employees.